Isolated myeloid sarcoma of the tibia - Serrado, Maria Ana; Proença, Ana Luísa; Alves, Pedro (BIRTH AND GROWTH MEDICAL JOURNAL, 2020)
Myeloid sarcoma is a rare tumor of immature myeloid cells in an extramedullary site which can be found in any part of the body. It may precede or concurrently occur with acute myeloid leukemia, chronic myeloid leukemia, or myeloproliferative disorders/myelodysplastic syndrome. Herein is reported the rare case of a child with myeloid sarcoma in the right tibia, without leukemic involvement at diagnosis. Diagnosis was challenging and several imaging modalities (radiography, computed tomography, magnetic resonance, bone scintigraphy, positron emitted tomography–computed tomography) were required. Additionally, three biopsies were necessary to make a definitive and conclusive diagnosis. With this case report, the authors intend to emphasize the need of considering myeloid sarcoma in the differential diagnosis of lytic bone lesions in children and highlight the high degree of clinical suspicion required when there is no leukemia evidence.